Designing Interactive Learning Media Using Mobile Augmented Reality for Electrical Circuit Education - Afdal Luthfi; Mukhlidi Muskhir; Hansi Effendi; Nizwardi Jalinus (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop interactive Augmented Reality (AR)-based learning media for electrical circuit courses. The method used is prototype development, with three stages: user needs analysis, prototype development, and pilot testing. In the first stage, the needs of users such as students and lecturers were identified through interviews and questionnaires, which showed 90.9% of students supported the use of AR to improve their understanding. The second stage involved designing 3D objects and their integration into the AR application using Blender and Unity. Testing was conducted through the black box method to assess the functionality of the application. The results showed that the application functioned well, especially in visualizing the concept of electrical circuits interactively. This application facilitates understanding through 3D simulations, videos, and practice questions, and can be accessed through mobile devices. In conclusion, this AR-based learning media is effective in supporting the teaching and learning process of electrical circuit courses.